On Using Ilities of Non-Functional Properties for Subsystems and Components - Lee, James; Collins, George (Systems (Basel), 2017)
The use of ilities for systems engineering of subsystems and components is investigated. Prior work on ilities has emphasized or restricted their application to system level, non-functional properties. The premise of this work is that ilities can be applied with benefit, and in some cases out of necessity, to lower levels of systems as well. The veracity of this premise is established by providing examples that demonstrate how some ilities are passed and used as a non-functional property of electrical and structural subsystems in aircraft. It is further demonstrated that flowing ilities down to the subsystem level is not only a useful practice for systems engineers, it can also be an essential step to ensure that customer needs are actually met by the system under design or service. Systems engineers often lack the detailed knowledge of the subsystems or components required to translate ilities into functional requirements. Thus, the system ilities are passed down and translated from non-functional to functional requirements by subject matter experts. We first discuss the definition, characteristics and scope of ilities. Then, we formulate the application of ilities at a subsystem level. Next, we show aircraft engineering examples for ilities applications. The application process is formalized with diagrams, and ilities’ relation to system architecture engineering is discussed. The work concludes with a summary and suggestions for future work.